2019
DOI: 10.1002/apj.2339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inlet shape on separation performance and flow‐field characteristics in a gas–solid cyclone separator

Abstract: The gas-solid separation experiments were conducted to compare separation performance between cyclone separators with different inlet shapes. Besides, the Reynolds stress model was employed to simulate flow field in different cyclones. The results revealed that the cyclone with a trapezoidal inlet could enhance separation efficiency without almost increasing pressure drop. Compared with the conventional rectangular inlet, a trapezoidal inlet had negligible effect on flow field of cyclone's separation space, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Their results showed that the use of an inlet double the size of the original case had the best performance, increasing the separation efficiency from 69.97% to 98.6%. The results of numerical and experimental studies by Wei et al [9] showed that by using a trapezoidal inlet channel, the separation efficiency was enhanced compared to that of a cyclone with a rectangular inlet channel, without increasing the pressure drop. Although it had little effect on the flow field inside the cyclone, it restrained particles near the vortex finder.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the use of an inlet double the size of the original case had the best performance, increasing the separation efficiency from 69.97% to 98.6%. The results of numerical and experimental studies by Wei et al [9] showed that by using a trapezoidal inlet channel, the separation efficiency was enhanced compared to that of a cyclone with a rectangular inlet channel, without increasing the pressure drop. Although it had little effect on the flow field inside the cyclone, it restrained particles near the vortex finder.…”
Section: Introductionmentioning
confidence: 99%